Development Of HOTS-Based Problems Instruments On Class 9 Curved Side Spaces Construction Materials - Damayanti, Safrida Dwi; Muhtarom , Muhtarom; Purwati , Heni (Universitas Mercu Buana Yogyakarta, 2023)
Students' Higher Order Thinking Skills (HOTS) in a public school in Semarang are still not optimal. According to Kurniasih (2020), one way to improve Higher Order Thinking Skills is by getting students used to practicing HOTS-based questions to develop students' higher-order thinking skills well. Therefore, this study aims to develop HOTS-based questions. This development uses the 4D steps developed by Thiagaraja, namely definition, design, development, and deployment. This research aims to develop a Higher Order Thinking Skills (HOTS)-based question instrument on curved side geometric shapes, so that it can support students' HOTS abilities. The results of the calculation of the agreement index given by the three experts obtained an average of 0.95. Therefore, the HOTS-based question instrument on curvilinear material is valid with a very high validity index